Environment-friendly composite plastic-wood plate and preparation method thereof

Through the use of modified wollastonite fibers and composite additives, the shortcomings of composite plastic wood boards in antibacterial properties and UV resistance are solved, and the material is efficient antibacterial, impact and UV resistance are achieved, and the service life is extended.

CN119570279AActive Publication Date: 2025-03-07HUIDONG MEIXIN PLASTIC LUMBER PROD MFG CO LTD

Patent Information

Application Number
CN202411841934.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing composite plastic wood boards have shortcomings in antibacterial and ultraviolet resistance, resulting in shortening of their service life and degradation of their performance.

Method used

Modified wollastonite fibers and composite additives are used to improve antibacterial properties through the modification of wollastonite fibers and Schiff base reaction, and improve impact resistance and UV resistance through polycaprolactone diol and benzophenone substances.

Benefits of technology

It significantly improves the antibacterial, impact resistance and UV resistance of composite plastic wood boards, extends its service life and improves performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570279A_ABST
    Figure CN119570279A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite plastic wood, and discloses an environment-friendly composite plastic wood plate and a preparation method thereof.The environment-friendly composite plastic wood plate is prepared from bamboo powder, poly (butylene adipate-co-terephthalate), polylactic acid, a compatilizer, filler, a lubricant, functional fibers and a composite additive, the functional fibers are added, so that the prepared environment-friendly plastic-wood plate has excellent mechanical properties and antibacterial properties, and the situation that the composite plastic-wood plate is eroded by bacteria and molds, and the appearance and the performance of the composite plastic-wood plate are affected badly can be avoided; by adding the composite additive, the prepared environment-friendly plastic-wood plate has excellent impact resistance and ultraviolet resistance, energy can be better absorbed and dispersed when the environment-friendly plastic-wood plate is impacted by external force, and the situation that the service life of the composite plastic-wood plate is shortened due to ultraviolet irradiation in the long-term use process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite plastic-wood, and in particular to an environmentally friendly composite plastic-wood board and a preparation method thereof. Background Art

[0002] Composite wood-plastic board, also known as wood-plastic composite board, has the advantages of both wood and plastic. It is mainly made of wood-based material mixed with thermoplastic polymer materials and other processing aids, and is prepared by heating, extruding and shaping. It has a long service life and good wear resistance. It can be prepared into floors, railings, fences, furniture, pallets, templates, etc., and is used in many fields such as construction, home, outdoor construction, agriculture, and logistics packaging. Thermoplastic polymer materials commonly used to prepare wood-plastic composite boards include polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), etc., but these polymer materials are all petroleum-based materials, non-degradable, and cause great pollution to the ecological environment. Therefore, research on degradable and environmentally friendly composite wood-plastic boards is of great practical significance.

[0003] Polybutylene adipate / terephthalate (PBAT) has excellent processing performance and degradability and can be used as the base material of composite plastic wood board. However, polybutylene adipate / terephthalate has poor antibacterial performance, which may cause the composite plastic wood board to be corroded by bacteria and mold, so that the appearance and performance are adversely affected; at the same time, polybutylene adipate / terephthalate has poor anti-ultraviolet performance. Long-term exposure to ultraviolet rays can easily cause the composite plastic wood board to fade, crack, and perform poorly, shortening the service life of the composite plastic wood board. Patent No. CN107987548B, Publication No. A high-strength wood-plastic composite material is developed, which includes the following raw materials: wood powder, bamboo powder, polyethylene, polyvinyl chloride, starch or modified starch, maleic anhydride grafted polyethylene, lubricant, and antioxidant. The prepared wood-plastic composite material has very good tensile strength and flexural strength. After adding modified starch, the tensile strength and flexural strength are greatly improved. However, the importance of antibacterial and anti-ultraviolet properties is not taken into account in the wood-plastic composite material. Therefore, the present invention provides an environmentally friendly composite wood-plastic board with degradability, excellent antibacterial and anti-ultraviolet properties and a long service life. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide an environmentally friendly composite plastic-wood board and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An environmentally friendly composite plastic-wood board comprises the following raw materials in parts by weight: 35-60 parts of bamboo powder, 30-55 parts of polybutylene adipate / terephthalate, 10-16 parts of polylactic acid, 2-5 parts of a compatibilizer, 1-3 parts of a filler, 1-4 parts of a lubricant, 3-6 parts of functional fibers, and 2-5 parts of a composite additive.

[0007] Furthermore, the particle size of the bamboo powder is 100-120 meshes; the compatibilizer is ethylene-methyl acrylate-glycidyl methacrylate; the filler is talcum powder; and the lubricant is zinc stearate.

[0008] Furthermore, the method for preparing the functional fiber comprises the following steps:

[0009] Step A: dispersing wollastonite fiber in dimethyl sulfoxide to form a uniform suspension, adding glyoxylic acid and a catalyst, raising the temperature to 90-100° C., reacting for 2-4 hours, cooling to room temperature, filtering, washing, and drying to obtain modified wollastonite fiber;

[0010] Step B: Add the modified wollastonite fiber to 1,4-dioxane, stir evenly, then add aminoguanidine hydrochloride and triethylamine, raise the temperature to 50-60°C, stir the reaction for 3-5h, separate the product, wash and dry to obtain functional fiber.

[0011] By adopting the above technical scheme, wollastonite is modified with glyoxylic acid, thereby introducing aldehyde groups on the surface of wollastonite to obtain modified wollastonite fibers. Under the action of triethylamine, the aldehyde groups on the surface of the modified wollastonite fibers can undergo Schiff base reaction with the amino groups in the aminoguanidine hydrochloride structure to obtain functional fibers.

[0012] Furthermore, in step A, the catalyst is p-toluenesulfonic acid or calcium methanesulfonate.

[0013] Furthermore, the preparation method of the composite additive comprises the following steps:

[0014] Step T1: adding polycaprolactone diol to N,N-dimethylformamide, stirring evenly, then adding 2,3-dimercaptosuccinic acid, 4-dimethylaminopyridine and dicyclohexylcarbodiimide, stirring and reacting at room temperature for 6-8 hours, separating the product to obtain an intermediate material;

[0015] Step T2: adding the intermediate material to dimethyl sulfoxide, mixing evenly, introducing nitrogen protection, adding 4-allyloxy-2-hydroxybenzophenone and a photoinitiator, reacting for 45-60 minutes under ultraviolet light with a power of 25-30 W and a wavelength of 365 nm, separating the product, and obtaining a composite additive.

[0016] By adopting the above technical scheme, the hydroxyl group in the polycaprolactone diol structure can undergo an esterification reaction with the carboxyl group in the 2,3-dimercaptosuccinic acid structure under the catalytic action of 4-dimethylaminopyridine and dicyclohexylcarbodiimide to obtain an intermediate material with a thiol group. Under the irradiation of ultraviolet light and the action of a photoinitiator, the thiol group in the intermediate material structure can undergo a thiol-ene click reaction with the olefinic group in the 4-allyloxy-2-hydroxybenzophenone structure to obtain a composite additive.

[0017] Furthermore, in step T1, the relative number average molecular weight of the polycaprolactone diol is 2000.

[0018] Furthermore, in step T2, the photoinitiator is benzoin dimethyl ether or benzoin isopropyl ether.

[0019] A method for preparing an environmentally friendly composite plastic-wood board comprises the following steps:

[0020] Step 1: Add bamboo powder, polybutylene adipate / terephthalate, polylactic acid, compatibilizer, filler, lubricant, functional fiber, and composite additives into a high-speed mixer, raise the temperature to 80-110° C., set the stirring rate to 350-600 r / min, stir and mix for 35-50 minutes, and obtain a mixed material;

[0021] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0022] Furthermore, in step 2, the hot pressing molding temperature is 160-190° C., and the molding pressure is 8-15 MPa.

[0023] Beneficial effects of the present invention:

[0024] (1) The functional fiber prepared by the present invention uses wollastonite fiber as the matrix. By modifying the wollastonite fiber, the problem of easy agglomeration of the wollastonite fiber is solved, and the compatibility problem between the wollastonite fiber and the matrix material is effectively improved. The wollastonite can be evenly dispersed in the matrix material and achieves a firm bond with the matrix material. The wollastonite fiber can give full play to its own advantages and improve the mechanical properties of the composite plastic-wood board. At the same time, the Schiff base reaction is used to introduce Schiff base groups and guanidine groups with antibacterial effects on the surface of the wollastonite fiber, thereby avoiding the problem of easy migration and precipitation of small molecule aminoguanidine hydrochloride antibacterial substances in the matrix material. The antibacterial properties of the composite plastic-wood board can also be improved, avoiding the erosion of bacteria and molds, causing adverse effects on the appearance and performance of the composite plastic-wood board, and shortening the service life of the composite plastic-wood board.

[0025] (2) The composite additive prepared by the present invention contains polycaprolactone diol with good toughness, which can significantly improve the impact resistance of the base material. At the same time, the composite additive can be cross-linked with the base material under the action of the compatibilizer to form a network structure, thereby improving the density of the structure and further improving the impact resistance of the composite plastic-wood board. When subjected to external force, it can better absorb and disperse energy to avoid damage to the base material. In addition, benzophenone substances with anti-ultraviolet function are introduced to effectively improve the anti-ultraviolet performance of the composite plastic-wood board, thereby preventing the composite plastic-wood board from being irradiated by ultraviolet rays during long-term use, resulting in fading, surface brittleness, cracks, etc., resulting in a shortened service life.

[0026] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 It is the infrared spectrum of the intermediate material and the composite additive in the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The preparation methods of the functional fibers and composite additives in the following examples and comparative examples are as follows:

[0031] 1. Preparation of functional fibers

[0032] Step A: 4.2 g of wollastonite fiber was dispersed in dimethyl sulfoxide to form a uniform suspension, 3 g of glyoxylic acid and 1.4 g of p-toluenesulfonic acid were added, the temperature was raised to 95° C., reacted for 4 h, cooled to room temperature, filtered, washed, and dried to obtain modified wollastonite fiber;

[0033] Step B: Add 4 g of modified wollastonite fiber to 1,4-dioxane, stir evenly, then add 2.8 g of aminoguanidine hydrochloride and 1.2 g of triethylamine, raise the temperature to 55°C, stir the reaction for 5 hours, separate the product, wash, and dry to obtain functional fiber.

[0034] The wollastonite fibers and functional fibers were analyzed using an ElementarVar io Micro cube elemental analyzer. The results showed that the wollastonite fibers did not contain nitrogen, while the nitrogen content in the functional fibers was 5.23%. Therefore, it can be seen that aminoguanidine hydrochloride was successfully grafted onto the surface of the wollastonite fibers to provide a nitrogen source.

[0035] 2. Preparation of composite additives

[0036] Step T1: 2 g of polycaprolactone diol with a relative number average molecular weight of 2000 is added to N,N-dimethylformamide, and after stirring evenly, 0.6 g of 2,3-dimercaptosuccinic acid, 0.1 g of 4-dimethylaminopyridine and 0.2 g of dicyclohexylcarbodiimide are added, and the mixture is stirred at room temperature for 6 hours, and the product is separated to obtain an intermediate material;

[0037] Step T2: 1.6 g of the intermediate material was added to dimethyl sulfoxide, mixed evenly, and nitrogen was introduced for protection. 0.5 g of 4-allyloxy-2-hydroxybenzophenone and 0.1 g of benzoin dimethyl ether were added. After reacting for 50 min under ultraviolet light with a power of 25 W and a wavelength of 365 nm, the product was separated to obtain a composite additive.

[0038] Use Fourier infrared spectrometer to conduct infrared testing on intermediate materials and composite additives, such as Figure 1 As shown in the figure, analysis shows that in the infrared spectrum of the intermediate material, 2561cm -1 、2538cm -1 The absorption peak of SH appeared at 1736 cm -1 The absorption peak of ester group C=O appears at 3412cm -1 The absorption peak of OH appeared at 3032 cm -1 The absorption peak of CH in the benzene ring appeared at 2561cm -1 The absorption peak of SH disappears at 1238cm -1 The absorption peak of COC appeared at

[0039] Example 1

[0040] Preparation of environmentally friendly composite plastic-wood board

[0041] Step 1: Add 35g of bamboo powder with a particle size of 120 mesh, 30g of polybutylene adipate / terephthalate, 10g of polylactic acid, 2g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of talc, 1g of zinc stearate, 3g of functional fiber, and 2g of composite additives into a high-speed mixer, raise the temperature to 80°C, set the stirring rate to 350r / min, stir and mix for 35min to obtain a mixed material;

[0042] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 160°C and the molding pressure is 10MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0043] Example 2

[0044] Preparation of environmentally friendly composite plastic-wood board

[0045] Step 1: Add 45g of bamboo powder with a particle size of 120 mesh, 40g of polybutylene adipate / terephthalate, 12g of polylactic acid, 3g of ethylene-methyl acrylate-glycidyl methacrylate, 1g of talc, 2g of zinc stearate, 4g of functional fiber, and 3g of composite additives into a high-speed mixer, raise the temperature to 90°C, set the stirring rate to 450r / min, stir and mix for 40min to obtain a mixed material;

[0046] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 170°C and the molding pressure is 12MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0047] Example 3

[0048] Preparation of environmentally friendly composite plastic-wood board

[0049] Step 1: Add 55g of bamboo powder with a particle size of 100 mesh, 50g of polybutylene adipate / terephthalate, 14g of polylactic acid, 4g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of talc, 3g of zinc stearate, 5g of functional fiber, and 4g of composite additives into a high-speed mixer, raise the temperature to 100°C, set the stirring rate to 550r / min, stir and mix for 45min, and obtain a mixed material;

[0050] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 180°C and the molding pressure is 14MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0051] Example 4

[0052] Preparation of environmentally friendly composite plastic-wood board

[0053] Step 1: Add 60g of bamboo powder with a particle size of 100 mesh, 55g of polybutylene adipate / terephthalate, 16g of polylactic acid, 5g of ethylene-methyl acrylate-glycidyl methacrylate, 3g of talc, 4g of zinc stearate, 6g of functional fiber, and 5g of composite additives into a high-speed mixer, raise the temperature to 110°C, set the stirring rate to 600r / min, stir and mix for 50min, and obtain a mixed material;

[0054] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 190°C and the molding pressure is 15MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0055] Comparative Example 1

[0056] Preparation of environmentally friendly composite plastic-wood board

[0057] Step 1: Add 55 g of bamboo powder with a particle size of 100 mesh, 50 g of polybutylene adipate / terephthalate, 14 g of polylactic acid, 4 g of ethylene-methyl acrylate-glycidyl methacrylate, 2 g of talc, 3 g of zinc stearate, and 5 g of functional fiber into a high-speed mixer, raise the temperature to 100° C., set the stirring rate to 550 r / min, stir and mix for 45 minutes, and obtain a mixed material;

[0058] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 180°C and the molding pressure is 14MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0059] Comparative Example 2

[0060] Preparation of environmentally friendly composite plastic-wood board

[0061] Step 1: Add 55g of bamboo powder with a particle size of 100 mesh, 50g of polybutylene adipate / terephthalate, 14g of polylactic acid, 4g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of talc, 3g of zinc stearate, and 4g of a composite additive into a high-speed mixer, raise the temperature to 100°C, set the stirring rate to 550r / min, stir and mix for 45min, and obtain a mixed material;

[0062] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 180°C and the molding pressure is 14MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0063] Comparative Example 3

[0064] Preparation of environmentally friendly composite plastic-wood board

[0065] Step 1: Add 55g of bamboo powder with a particle size of 100 mesh, 50g of polybutylene adipate / terephthalate, 14g of polylactic acid, 4g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of talc, 3g of zinc stearate, 5g of wollastonite fiber, and 4g of composite additives into a high-speed mixer, raise the temperature to 100°C, set the stirring rate to 550r / min, stir and mix for 45min to obtain a mixed material;

[0066] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 180°C and the molding pressure is 14MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0067] Comparative Example 4

[0068] Preparation of environmentally friendly composite plastic-wood board

[0069] Step 1: Add 55g of bamboo powder with a particle size of 100 mesh, 50g of polybutylene adipate / terephthalate, 14g of polylactic acid, 4g of ethylene-methyl acrylate-glycidyl methacrylate, 2g of talc, 3g of zinc stearate, 5g of functional fiber, and 4g of 4-allyloxy-2-hydroxybenzophenone into a high-speed mixer, raise the temperature to 100°C, set the stirring rate to 550r / min, stir and mix for 45min, and obtain a mixed material;

[0070] Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. The molding temperature is 180°C and the molding pressure is 14MPa. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

[0071] Performance Testing

[0072] The environmentally friendly composite plastic wood boards prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were made into samples that met the test standards. The tensile strength of the samples was tested according to the standard GB / T 1040.1-2018. The impact strength of the samples was tested according to the standard GB / T 1843-2008. After the samples were placed for 60 days, they were placed under a UVB-313 type ultraviolet fluorescent lamp tube for 800 hours of irradiation and aging according to the standard GB / T 16422.2-2022. The formula △E=[(△L) 2 +(△a) 2 +(△b) 2 ] 1 / 2 Calculate the color difference △E. The larger the △E value, the worse the anti-ultraviolet performance and the more serious the aging. Refer to the antibacterial test in the standard JC / T 2039-2010 to test the antibacterial rate of the sample. The test results are shown in the following table:

[0073]

[0074] As can be seen from the above table, the environmentally friendly composite plastic wood boards prepared in Examples 1 to 4 of the present invention have excellent mechanical properties, impact resistance, antibacterial properties and anti-ultraviolet properties; Comparative Example 1 adds functional fibers without adding composite additives, and has excellent mechanical properties and antibacterial properties, but poor impact resistance and anti-ultraviolet properties; Comparative Example 2 adds composite additives without adding functional fibers, and has excellent impact resistance and anti-ultraviolet properties, but poor mechanical properties and antibacterial properties; Comparative Example 3 adds wollastonite fibers and composite additives, and the wollastonite fibers are directly added without modification. The addition of functional fiber and 4-allyloxy-2-hydroxybenzophenone has excellent mechanical properties and antibacterial properties, but 4-allyloxy-2-hydroxybenzophenone is a small molecule anti-ultraviolet substance and has migration and precipitation phenomena, so the anti-ultraviolet performance is poor, and the polycaprolactone diol cannot be cross-linked with the matrix to form a network structure to improve the impact resistance, so the impact resistance is poor.

[0075] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly composite plastic-wood board, characterized in that: The invention comprises the following raw materials in parts by weight: 35-60 parts of bamboo powder, 30-55 parts of polybutylene adipate / terephthalate, 10-16 parts of polylactic acid, 2-5 parts of compatibilizer, 1-3 parts of filler, 1-4 parts of lubricant, 3-6 parts of functional fiber and 2-5 parts of composite additives.

2. The environmentally friendly composite plastic-wood board according to claim 1, characterized in that: The particle size of the bamboo powder is 100-120 meshes; the compatibilizer is ethylene-methyl acrylate-glycidyl methacrylate; the filler is talcum powder; and the lubricant is zinc stearate.

3. The environmentally friendly composite plastic-wood board according to claim 1, characterized in that: The preparation method of the functional fiber comprises the following steps: Step A: dispersing wollastonite fiber in dimethyl sulfoxide to form a uniform suspension, adding glyoxylic acid and a catalyst, raising the temperature to 90-100° C., reacting for 2-4 hours, cooling to room temperature, filtering, washing, and drying to obtain modified wollastonite fiber; Step B: Add the modified wollastonite fiber to 1,4-dioxane, stir evenly, then add aminoguanidine hydrochloride and triethylamine, raise the temperature to 50-60°C, stir the reaction for 3-5h, separate the product, wash and dry to obtain functional fiber.

4. The environmentally friendly composite plastic-wood board according to claim 3, characterized in that: In step A, the catalyst is p-toluenesulfonic acid or calcium methanesulfonate.

5. The environmentally friendly composite plastic-wood board according to claim 1, characterized in that: The preparation method of the composite additive comprises the following steps: Step T1: adding polycaprolactone diol to N,N-dimethylformamide, stirring evenly, then adding 2,3-dimercaptosuccinic acid, 4-dimethylaminopyridine and dicyclohexylcarbodiimide, stirring and reacting at room temperature for 6-8 hours, separating the product to obtain an intermediate material; Step T2: adding the intermediate material to dimethyl sulfoxide, mixing evenly, introducing nitrogen protection, adding 4-allyloxy-2-hydroxybenzophenone and a photoinitiator, reacting for 45-60 minutes under ultraviolet light with a power of 25-30 W and a wavelength of 365 nm, separating the product, and obtaining a composite additive.

6. The environmentally friendly composite plastic-wood board according to claim 5, characterized in that: In step T1, the relative number average molecular weight of the polycaprolactone diol is 2000.

7. The environmentally friendly composite plastic-wood board according to claim 5, characterized in that: In step T2, the photoinitiator is benzoin dimethyl ether or benzoin isopropyl ether.

8. A method for preparing an environmentally friendly composite plastic-wood board as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add bamboo powder, polybutylene adipate / terephthalate, polylactic acid, compatibilizer, filler, lubricant, functional fiber, and composite additives into a high-speed mixer, raise the temperature to 80-110° C., set the stirring rate to 350-600 r / min, stir and mix for 35-50 minutes, and obtain a mixed material; Step 2: Put the mixed material into a twin-screw extruder to melt and extrude the masterbatch. The masterbatch is passed through a flat vulcanizer and hot-pressed. After cooling, it is cut to obtain an environmentally friendly composite plastic-wood board.

9. The method for preparing an environmentally friendly composite plastic-wood board according to claim 8, characterized in that: In step 2, the hot pressing molding temperature is 160-190° C., and the molding pressure is 8-15 MPa.

Citation Information

Patent Citations

  • A high-strength wood-plastic composite material

    CN107987548B

  • Bamboo powder filling biodegradable compound material and preparation method thereof

    CN101942184A

  • Continuous long fiber reinforced polyolefin plastic wood composite material and preparation method thereof

    CN102002178A

  • Wollastonite fiber with large length-diameter ratio and preparation method thereof

    CN102249530A

  • Modification method for flexible wollastonite fiber

    CN105297431A

Cited By

  • PVC composite material with antibacterial effect and preparation method thereof

    CN119978659A

  • Lightweight high-strength plastic material and preparation method thereof

    CN120157990A

  • Lightweight high-strength plastic material and method for its production

    CN120157990B